Mengenal Manhaj Tafsir Fazrul Rahman - Badruzzaman M. Yunus; Muhammad Rizaldi Syahputra; Asep Sufian Sya'roni (UIN Sunan Gunung Djati Bandung, 2021)
This research on Manhaj Tafsir Fazlur Rahman aims to describe and describe the methods or approaches used by Fazlur Rahman in interpreting the Qur'an. This research was conducted through library research. The study is descriptive and analytical, that is, analytical in a historical and philosophical sense. Data concerning the methodological thinking of interpreting the Koran can be traced back to Rahman's writing (primary source). The research data is in the form of works by Fazlur Rahman in interpreting various Qur'an verses. Meanwhile, the data sources that will be explored in this paper are Rahman's interpretations, which are widely published in multiple books in Indonesia. The results of his research show that diversity in both the method (manhaj / tariqah), style (nau'), and approaches (alwan) used is something that cannot be avoided in a work of interpretation. Although interpretive works have appeared in modern times, their interpretation still follows classical and medieval patterns. For Fazrul Rahman, tafsir's essence is how an interpreter can create an authentic meaning (original meaning) from reading through the historical context of the past. He captures all moral aspects to contextualize meaning in the present with a new methodology.